2008
DOI: 10.1111/j.1600-0501.2008.01534.x-i2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local and systemic factors on the incidence of late oral implant loss

Abstract: Background: This retrospective study was set to assess the influence of systemic and local bone and intra‐oral factors on the occurrence of implant loss from abutment connection up to 2 years. Materials and methods: The files of 700 patients, have been collected randomly from the total patient group treated by means of endosseous Brånemark® system implants (Nobel Biocare, Gothenburg, Sweden) at the Department of Periodontology of the University Hospital of the Catholic University of Leuven. The end point obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 33 publications
1
26
0
2
Order By: Relevance
“…From the 14 studies, a total of 1,260 dental implants were inserted in diabetic patients, with 49 failures (3.89%), and 11,476 implants were inserted in non-diabetic patients, with 555 failures (4.84%). Six studies (Keller et al, 1999;Morris et al, 2000;van Steenberghe et al, 2002;Doyle et al, 2007;Bell et al, 2011;Levin et al, 2011) did not inform whether there was a statistically significant difference or not for the implant failure rates between non-diabetic and diabetic patients, whereas the other 5 studies (Accursi, 2000;Alsaadi et al, 2008b;Tawil et al, 2008;Anner et al, 2010;Le et al, 2013) did not find a statistically significant difference. One study (Alsaadi et al, 2008a) compared the implant failure rates for the non-diabetic patients with the type 1 and type 2 diabetic patients separately, with statistical and nonstatistical The study was an RCT for immediately vs. loaded implants but not for diabetic and non-diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…From the 14 studies, a total of 1,260 dental implants were inserted in diabetic patients, with 49 failures (3.89%), and 11,476 implants were inserted in non-diabetic patients, with 555 failures (4.84%). Six studies (Keller et al, 1999;Morris et al, 2000;van Steenberghe et al, 2002;Doyle et al, 2007;Bell et al, 2011;Levin et al, 2011) did not inform whether there was a statistically significant difference or not for the implant failure rates between non-diabetic and diabetic patients, whereas the other 5 studies (Accursi, 2000;Alsaadi et al, 2008b;Tawil et al, 2008;Anner et al, 2010;Le et al, 2013) did not find a statistically significant difference. One study (Alsaadi et al, 2008a) compared the implant failure rates for the non-diabetic patients with the type 1 and type 2 diabetic patients separately, with statistical and nonstatistical The study was an RCT for immediately vs. loaded implants but not for diabetic and non-diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Detailed data of the 14 included studies are listed in Tables 1 and 2. The meta-analysis included 7 controlled clinical trials (Morris et al, 2000;van Steenberghe et al, 2002;Dowell et al, 2007;Alsaadi et al, 2008a;Tawil et al, 2008;Levin et al, 2011;Grandi et al, 2013) and 7 retrospective analyses (Keller et al, 1999;Accursi, 2000;Doyle et al, 2007;Alsaadi et al, 2008b;Anner et al, 2010;Bell et al, 2011;Le et al, 2013). The study of Grandi et al (2013) was a randomized clinical trial for immediately vs. early loaded implants but not for diabetic vs. non-diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the failures occurred during the first year after implant replacement. 32 Another valid alternative is to do a hybrid toothimplant-supported fixed partial denture. In a systematic review, Weber and Sukotjo have shown that, after an observation period of at least six years, implant survival and prosthetic success were similar for implant supported and tooth to implant supported prostheses.…”
Section: Explantation:-mentioning
confidence: 99%